RECONSTITUTIONALITY OF THE 1945 CONSTITUTION AFTER THE FOURTH AMENDMENT - Iskandar, Rusli Kustiaman; Yusdiansyah, Efik; Hidayat, Asyhar (International Journal of Research -GRANTHAALAYAH, 2019)
The four amendments to the 1945 Constitution are imperatives of an imperfect human work. For Indonesia, the 1945 Constitution is the highest law (basic law) of all existing state norms and institutions. However, after careful scrutiny, it turns out that there are a number of provisions that weaken the constitutionality of the 1945 Constitution. The purpose of this article is to analyze the constitutionality of the 1945 Constitution after the fourth amendment. The method used is descriptive method and the method of constitutional comparison, with a qualitative juridical analysis approach to state administration. The conclusion of this article is that there are provisions that weaken the 1945 Constitution such as the 42 state affairs, government and state administration that submit further arrangements to the law. In addition, and especially if it is associated with the authority to change and develop itself, it becomes very dependent on the DPR. For this reason it is important to do constitutionality by making changes to the fifth and so on, beginning with compiling a grand design change that emphasizes legal and constitutional aspects rather than political aspects.